2012
DOI: 10.1590/s0100-69162012000200003
|View full text |Cite
|
Sign up to set email alerts
|

Substrate with Organosuper® for cucumber seedlings formation in protected environments and polystyrene trays

Abstract: Culture environments, trays and doses of organic compost were evaluated in the formation of cucumber seedlings (Cucumis sativus L.). Five environmental conditions were tested: (A1) a greenhouse with height of 2.5 m, covered with polyethylene film, (A2) nursery with height of 2.5 m, monofilament fabric, 50% shading, (A3) nursery with height of 2.5 m, heat-reflective screen, 50% shading, (A4) nursery with a height of 1.8 m, covered with coconut tree straw and (A5) greenhouse with height of 4.0 m, covered with po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 10 publications
0
4
0
3
Order By: Relevance
“…Uptake of nutrients, water and dry matter production are affected by the restriction of the roots and thus the volume of substrate that is determined by the container size is an important factor for adequate growth of the seedlings. Costa et al (2012) found that tray of 72 cells was the best container for production of cucumber seedlings, promoting more vigorous plants in substrate with soil and 7 or 14% organic compound.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Uptake of nutrients, water and dry matter production are affected by the restriction of the roots and thus the volume of substrate that is determined by the container size is an important factor for adequate growth of the seedlings. Costa et al (2012) found that tray of 72 cells was the best container for production of cucumber seedlings, promoting more vigorous plants in substrate with soil and 7 or 14% organic compound.…”
Section: Resultsmentioning
confidence: 97%
“…Different types of recipients are used for seedling production (test tubes, trays, plastic bags), made from different materials (including expanded polystyrene, polypropylene) and sizes, especially expanded polystyrene trays that are the most used for cucumber seedling production (FILGUEIRA, 2008). The volume of the cavity is one of the most obvious and important characteristics of a container because in general, the larger the container the larger the seedling that can be produced (ECHER et al, 2007;COSTA et al, 2012;. However, the optimum container size varies according to many different factors, including species, growing density, environmental conditions and length of the growing season (TSAKALDIMI et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Maiores produções de alface, beterraba e pepino foram encontradas quando as mudas foram produzidas em recipientes com maior volume de célula (Leal et al 2011;Costa et al 2012). Godoy & Cardoso (2005) observaram maior número de folhas e produção total de couve flor proveniente do transplante de mudas produzidas em bandejas de 128 células.…”
Section: Resultsunclassified
“…The final quality of an agricultural product is the result of several factors, among them the development of more vigorous seedlings because it is one of the most important stages in agricultural production, with a direct effect on crop cycle and productivity. In this context, crop container care is essential for obtaining quality plants as it directly affects root system growth, influencing nutrient absorption capacity, harvest time, and the number of possible cycles per year (Costa et al, 2012). Thus, the aim of this study was to assess the variation of the surface temperature of trays and substrate in the production of lettuce seedlings and its influence on the final product.…”
Section: Introductionmentioning
confidence: 99%